Impact of a Didactic Sequence Based on Narrative Texts on the Development of Literary and Environmental Competencies in Secondary School Students (Papeles, 2026)
Introduction: In the context of climate change, global warming, and pollution affecting water, air, and soil, it is essential to promote Education for Sustainable Development (ESD), as it fosters skills that enhance environmental care, critical thinking, and human sensitivity. However, this requires the design and implementation of sequenced educational activities aligned with these goals. This study investigates the extent to which the implementation of a didactic sequence based on narrative texts can improve students’ literary and environmental competence. The objective was to evaluate the impact of the sequence on the development of these abilities in eighth-grade students (second year of secondary school). Methodology: The study employed a mixed-methods approach, a quasi-experimental design, and a correlational scope. The population consisted of intact groups (an experimental group and a control group comprising 15 and 17 students, respectively) from Centro Educativo en Artes Monseñor Francisco Panal, located in the community of La Joya, San Francisco de Macorís, Dominican Republic. Observation and survey techniques were used for data collection through two questionnaires, a field diary, and an analytical rubric. The intervention was implemented through a socio-formative instructional sequence based on eco-stories. Following the administration of the post-test, a mixed ANOVA, Levene’s test, and Shapiro–Wilk test were conducted.  Results and discussion: The results revealed a significant improvement in the experimental group’s literary and environmental competence, both quantitatively and qualitatively. Conclusion: The mixed ANOVA and the systematic observations demonstrated that the didactic sequence was the cause of the improvement of skills in these students.
Keywords: Reading; literary competence; environmental education; environmental narratives; ecocritical